Effect of Different Drying Methods on Nutrient Quality of the Yellow Mealworm (Tenebrio molitor L.) - Kröncke, Nina (Insects, 2019)
Yellow mealworm (Tenebrio molitor L.) represents a sustainable source of proteins and fatty acids for feed and food. Industrial production of mealworms necessitates optimized processing techniques, where drying as the first postharvest procedure is of utmost importance for the quality of the final product. This study examines the nutritional quality of mealworm larvae processed by rack oven drying, vacuum drying or freeze drying, respectively. Proximate composition and fatty acid profile were comparable between the dried larvae. In contrast, larvae color impressions and volatile compound profiles were very much dependent on processing procedure. High-temperature rack oven drying caused pronounced darkening with rather low content of volatiles, pointing toward the progress of Maillard reaction. On the other hand, vacuum drying or freeze drying led to enrichment of volatile Maillard reaction and lipid oxidation intermediates, whose actual sensory relevance needs to be clarified in the future. Beyond sensory and visual importance drying intermediates have to be considered with regard to their metal ion chelating ability; in particular for essential trace elements such as Zn(2+). This study found comparable total zinc contents for the differently dried mealworm samples. However, dried larvae, in particular after rack oven drying, had only low zinc accessibility, which was between 20% and 40%. Therefore, bioaccessibility rather than total zinc has to be considered when their contribution to meeting the nutritional requirements for zinc in humans and animals is evaluated.